Chemical composition and antimicrobial activities of the essential oils ofCinnamomum aureofulvum Gamb. - Mohd Ali, Nor Azah; Mohtar, Mastura; Shaari, Khozirah; Rahmanii, Mawardi; Ali, A. Manaf; Jantan, Ibrahim (Taylor and Francis Group, 2002)
The leaf and bark oils of Cinnamomum aureofulvum Gamb. were analyzed by GC and GC/MS. The leaf oil was made up predominantly of benzyl benzoate (43.5%), benzyl alcohol (8.1%) and linalool (7.3%), whereas the bark oil contained cinnamaldehyde (46.6%), linalool (14.6%) and eugenol (5.0%) as the major components. The oils were screened for antibacterial activity against two Gram positive bacteria (Staphylococcus aureus and S. epidermidis) and two Gram negative bacteria (Pseudomonas cepacia and P. aeruginosa) and antifungal activity against two Candida species (C. albicans and C. glabrata) and three dermatophytes (Microsporum canis, Trichophyton mentagrophytes and T. rubrum) by using the broth microdilution method. The oils exhibited insignificant activity against all the bacteria except P. aeruginosa, which was observed to be sensitive to the bark oil with MIC value of 1.87 μg/μL. They demonstrated moderate to strong activities towards all the fungi tested except C. glabrata, with MIC values ranging from 0.63 to 2.50 μg/μL. Among the fungi, M. canis was the most susceptible, with both oils exhibiting their lowest MIC values towards the fungi. The bark oil was found to be more effective than the leaf oil and their activity was mainly due to their respective major components.